KRISTUS YESUS MODEL HIDUP SETIAP KRISTEN : Satu Refleksi atas Surat Filipi - Mahulae, Kristinus C (UNIKA Santo Thomas, 2008)
By reflecting the hymn of the Christians, Paul has found that although Jesus possessed divine equality, and its consequent privilege to appear like Yahweh in glory, he did not stand on his dignity. Jesus did not treat the states of divine glory (i.e. being equal with God) as a privilege or possession to be clutched so tenaciously that it might be exploited in the future. Jesus renounced his heavenly claims, assumed the humblest human position, even died on the cross. As a consequence “God has highly exalted him” (Phi 2: 9a) and “God bestowed on him the name which is above every name” (Phi 2: 9b). Jesus made himself ‘obedient’ and as a consequence God gave him authority over those in heaven and on earth and under the earth”. By using the hymn of the first Christians considering the life of the Philippians Paul asked them to be in humility and self-sacrifice in their relations with one another. Paul exhorted them in daily life to give way to the views, wishes of others and making yourself appear unimportant. Paul asked them to have the same attitude toward each other as the attitude you have to Christ. Do not attempt to dominate the rest, but rather have the closest sympathy with their needs and interests. The believers should consider other better than themselves. Others are truly better than them, since they are manifestations of God or of Christ. Paul urged the Christians to contemplate the whole story of Christ, so that they could live as Christians, as the followers of Christ.